2001
DOI: 10.1289/ehp.01109629
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic in drinking water and pregnancy outcomes.

Abstract: We studied a group of women of reproductive age (15-49 years) who were chronically exposed to arsenic through drinking water to identify the pregnancy outcomes in terms of live birth, stillbirth, spontaneous abortion, and preterm birth. We compared pregnancy outcomes of exposed respondents with pregnancy outcomes of women of reproductive age (15-49 years) who were not exposed to arsenic-contaminated water. In a cross-sectional study, we matched the women in both exposed and nonexposed groups for age, socioecon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
131
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 320 publications
(134 citation statements)
references
References 9 publications
3
131
0
Order By: Relevance
“…A larger cross-sectional study (Ahmad et al, 2001), reported increased PD for 359 pregnancies in 96 women (Table 2) consuming water contaminated by >50 μg/L iAs for at least five years, compared to 309 pregnancies in 96 referents exposed to <20 μg/L iAs (PPR = 2.54, P = 0.018). The sample size was determined a priori to ensure adequate statistical power.…”
Section: Resultsmentioning
confidence: 98%
“…A larger cross-sectional study (Ahmad et al, 2001), reported increased PD for 359 pregnancies in 96 women (Table 2) consuming water contaminated by >50 μg/L iAs for at least five years, compared to 309 pregnancies in 96 referents exposed to <20 μg/L iAs (PPR = 2.54, P = 0.018). The sample size was determined a priori to ensure adequate statistical power.…”
Section: Resultsmentioning
confidence: 98%
“…Ahmad et al (2001) also found an inverse association between arsenicosis and SES and education level, probably due to the lack of access to As-free water. In other studies, As was also related to nutritional status of participants.…”
Section: Discussionmentioning
confidence: 81%
“…A slight non-significant increased risk (OR 1.10, 95% CI 0.91 to 1.33) was associated with living in an arsenic-exposed township in Taiwan 13. A cross-sectional study in Bangladesh found significantly higher rates of preterm birth among women living in an arsenic-affected village when compared with women living in a village with arsenic ≤20 μg/l 16. The same study reported stillbirth rates about 2.5 times higher in the arsenic-affected village, which we did not find in our study.…”
Section: Discussionmentioning
confidence: 99%